A bond never broken eaudiobook Daughters of amana series, book 3. - Miller, Judith (Daughters of Amana, 2011)
Best-selling author Judith Miller sets this compelling novel in 1917 Iowa. With the Great War fueling anti-German hysteria, agents of President Wilson's Council of National Defense threaten to disfigure Jutta Schmidt, torch her family's bakery, and butcher her parents unless she returns to the Amana colonies as their spy. Back in South Amana, she's befriended by Ilsa Redlich and her family. But if she overhears antiwar remarks, how can she betray these kind people?